2015
DOI: 10.1177/0885328214568467
|View full text |Cite
|
Sign up to set email alerts
|

Poly-3-hydroxybutyrate-co-3-hydroxyvalerate containing scaffolds and their integration with osteoblasts as a model for bone tissue engineering

Abstract: Nano/micro engineered polymeric materials offer expansive scope of biomimetic scaffolds for bone tissue engineering especially those involving electrospun biodegradable nanofibers incorporated with inorganic nanoparticles, thus mimicking the extracellular matrix of bone both structurally and chemically. For the first time, poly-3-hydroxybutyrate-co-3-hydroxyvalerate containing natural poly-(α, β)-DL-aspartic acid and inorganic hydroxyapatite nanofibers were fabricated using poly-3-hydroxybutyrate-co-3-hydroxyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…But as mentioned, PHBV completely degraded and consumed by the body's cells and its degradability test was positive, whereas after degradation in the body becomes a nontoxic 3‐hydroxybutyrate, as a natural blend of the blood (Gheibi, Khoshnevisan, Ketabchi, Derakhshan, & Babadi, ). Studies showed that PHB formability and processability were improved when changed to the PHBV, making it usable in regenerative medicine and tissue engineering (Singh, Sharma, & Malviya, ; S. Zhang, Prabhakaran, Qin, & Ramakrishna, ). In this study, a PHBV nanofibrous scaffold was fabricated by electrospinning and the SEM results confirmed its fibrous structure in nanometer scale, and its biocompatibility was also confirmed using culturing human iPSCs and MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…But as mentioned, PHBV completely degraded and consumed by the body's cells and its degradability test was positive, whereas after degradation in the body becomes a nontoxic 3‐hydroxybutyrate, as a natural blend of the blood (Gheibi, Khoshnevisan, Ketabchi, Derakhshan, & Babadi, ). Studies showed that PHB formability and processability were improved when changed to the PHBV, making it usable in regenerative medicine and tissue engineering (Singh, Sharma, & Malviya, ; S. Zhang, Prabhakaran, Qin, & Ramakrishna, ). In this study, a PHBV nanofibrous scaffold was fabricated by electrospinning and the SEM results confirmed its fibrous structure in nanometer scale, and its biocompatibility was also confirmed using culturing human iPSCs and MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…Among the biodegradable, biocompatible, and thrombus‐resistant polymers, of special note are the polyhydroxyalkanoates (PHA), of which poly‐3‐hydroxybutyrate (PHB) is the most widely studied polymer . PHB is currently used to develop a range of medical products for dentistry, cardio surgery, orthopedics, and other areas …”
Section: Introductionmentioning
confidence: 99%
“…3 PHB is currently used to develop a range of medical products for dentistry, cardio surgery, orthopedics, and other areas. [4][5][6] It is well known that implants can promote restoration of damaged connective tissue and ensure the performance of its function. Of special interest are synthetic polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymers include a broad spectrum of biostable polymers, for example polyethylene terephthalate [9], polytetrafluoroethylene [22] and polyurethane, suitable for fabrication of vascular grafts [23], and biodegradable polymers, for example polylactides (PLA) [24,25] and their copolymers with polyglycolides (PLGA) [1,26], polycaprolactone (PCL) [2,4,6], poly-3-hydroxybutyrate-co-3-hydroxyvalerate (PHBV) [27], polydioxanone [5], polyvinylalcohol (PVA) [28,29], and synthetic peptides [7,30].…”
Section: Introductionmentioning
confidence: 99%
“…This is feasible by addition of inorganic nanoparticles into nanofibers, such as ceramic nanoparticles, for example hydroxyapatite [16,27,28,30], tricalcium phosphate [63,66], calcium oxide [67], or calcium silicate [24]; metal-based nanoparticles, for example gold nanoparticles [29], ferro- [62], or nanodiamonds [68]. These nanoparticles not only reinforce the polymeric nanofibers but also enhance their bioactivity in terms of increased cell adhesion, growth, osteogenic cell differentiation, bone matrix mineralization and antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%